2014
DOI: 10.1186/1477-7819-12-193
|View full text |Cite
|
Sign up to set email alerts
|

Is concomitant splenectomy beneficial for the long-term survival of patients with gastric cancer undergoing curative gastrectomy? A single-institution study

Abstract: BackgroundCurative resection is the treatment of choice for gastric cancer, but it is unclear whether gastrectomy should also include splenectomy. We retrospectively analyzed long-term survival in patients in our hospital who underwent gastrectomy plus splenectomy (G + S) or gastrectomy alone (G-A) for gastric cancer.MethodsWe identified 214 patients who underwent surgery with curative intent between 1980 and 2003. Of these, 100 underwent G + S, and 114 underwent G-A. The primary endpoint was 5-year overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…There was no significant difference in mortality in four studies (20,22,23,26); however, one study showed barely significant difference in mortality between gastrectomy with and without splenectomy (2.7% vs. 0.4%, respectively, p=0.048) (19). The remaining three studies did not report the outcomes of mortality (22,24,25). All studies showed the superiority of spleen preservation for OS by univariate analysis; however, three studies showed no significant between-group difference in OS on sub-group analysis disaggregated by disease stage (19)(20)(21).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…There was no significant difference in mortality in four studies (20,22,23,26); however, one study showed barely significant difference in mortality between gastrectomy with and without splenectomy (2.7% vs. 0.4%, respectively, p=0.048) (19). The remaining three studies did not report the outcomes of mortality (22,24,25). All studies showed the superiority of spleen preservation for OS by univariate analysis; however, three studies showed no significant between-group difference in OS on sub-group analysis disaggregated by disease stage (19)(20)(21).…”
Section: Resultsmentioning
confidence: 96%
“…A total of eight retrospective studies (combined n=3,676) showed the beneficial effect of spleen-preserving gastrectomy. Of these, four articles were published from Korea (19)(20)(21)(22), three were from China (23)(24)(25) and one was from Germany (26). In four studies, the incidence of postoperative morbidity was significantly higher in the splenectomy compared to the non-splenectomy groups (19,21,22,25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the randomized controlled trial of Toge et al (1985) splenectomy had positive effect on overall survival compared to the non-splenectomy group (71.7% vs 56%). However, at some retrospective studies, splenectomy had a negative effect on overall survival (Ito et al, 2013;Nashimoto et al, 2012;Zhang et al, 2014). Another important issue is station 10 lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The immune function of the spleen against cancer is unclear. A large‐scale cohort study (mostly involving patients undergoing splenectomy for treatment of trauma) 23 demonstrated a high risk of cancer development in the long‐term follow up. However, the relationship of splenectomy with cancer recurrence has not been clearly shown.…”
Section: Previous Reports On Presence or Absence Of Splenectomy And Dmentioning
confidence: 99%